Urban Heat Island Literacy Among Geography Education Students of Universitas Muhammadiyah Surakarta - Siti Azizah Susilawati; Mohd Hairy Ibrahim; Nor Md Isa Kalsum Binti Md Isa; Muhammad Musyiam; Nanda Khoirunisa (Universitas Negeri Medan, 2024)
Geography Education students are expected to have literacy about the phenomena around them, one of which is Urban Heat Island (UHI) literacy. It is appropriate by the mission of Geography Education at the Muhammadiyah University of Surakarta (UMS) is to produce geography educators with a view on disaster mitigation. This study aims to determine the UHI literacy of students in 7th semester, Deparment Geography Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta. This research is a quantitative descriptive study with survey methods. The study using purposive random sampling of 80 respondents and as many as 54 collage students were selected as samples. The UHI literacy research instrument was developed based on the OECD's International Program for Student Assessment (PISA) in 1999. Based on the indicators in scientific literacy which are divided into three categories, the results are obtained: 1) Indicators of UHI's concepts show that high categories are middle class 20.4 % and the majority of students at a high level with 79.6%; 2) Indicators of UHI's processes obtained results with 1.8 % of students at a low level, 20.4 % of students at a medium level, and 78.8 % at a high level; 3) UHI's situation indicators showed that the high category was 93% and moderate was 7%. The conclusion shows that the UHI literacy of students is relatively high, indicating that curriculum based on disaster insight has been doing well, but further research is needed on other disaster insights and analysis of factors which affect the results above.Keywords: Urban Heat Island, Urban Heat Island Literacy, Curriculum